PERBANDINGAN KINERJA MOBIL MENGGUNAKAN BAHAN BAKAR MINYAK (BBM) DAN BAHAN BAKAR GAS (BBG) - Zainulsjah .; A. C. Arya; Senoadi . (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2016)
Vehicle population in Indonesia which are fueled by oil increase annually while the petroleum reserves are more limited. Parallel with the increasing oil fuel consumption for the vehicles causing the increasing fuel subsidies and air pollution as well. To reduce the subsidy for oil fuel and the air pollution it is necessary to find out the alternative fuel which is environmentally friendly as a vehicle fuel and are available in huge amount. One of the alternative fuels which is environmentally friendly is the gas fuel. The problems for developing the use of gas fuel are that the availibility of the filling stations are still limited and the users feel unsafe to use the gas fuel. The research results showed at dynamometer (dynotest) that the gas fuel can be used as a alternative fuel for oil but unfortunately the vehicle designed has a declined torque at variable rotation (rpm) and a decrease Pouzer to variable rotation and exhaust emission is very environmental friendly (good) especially causes by decreasing emissions of CO, CO2, HC and O2 and increasing Lamda.